Effect of the association between citric acid and EDTA on root surface etching - Leite, Fabio Renato Manzolli; Nascimento, Gustavo Giacomelli; Leite, Elza Regina Manzoli; Leite, Amauri Antiqueira; Sampaio, José Eduardo Cezar [UNESP] (Jaypee Brothers Medical Publishing, 2013)
Objective: This study aims to compare the clot stabilization on root surfaces conditioned with citric acid and ethylenediaminetetraacetic acid (EDTA). Materials and methods: Scaled root samples (n = 100) were set in five groups: group I?control group (saline solution); group II (24% EDTA); group III (25% citric acid); group IV (EDTA + citric acid); group V (citric acid + EDTA). Fifty samples were assessed using the root surface modification index (RSMI). The other 50 received a blood drop after conditioning. Clot formation was assessed using blood elements adhesion index (BEAI). A blind examiner evaluated photomicrographs. Statistical analysis considered p < 0.05. Results: Groups-III and G-V attained the best results for RSMI and BEAI in comparison to control. The worst results for clot stabilization were seen in group-II. EDTA employment before citric acid (group-IV) reduced clot formation in comparison to citric acid use alone (group-III). Conclusion: Root conditioning with citric acid alone and before EDTA had the best results for smear layer removal and clot stabilization. EDTA inhibited clot stabilization on root surface and must have a residual activity once it has diminished clot adhesion to root even after citric acid conditioning. Thus, EDTA can be used to neutralize citric acid effects on periodontal cells without affecting clot stabilization. Clinical significance: To demonstrate that citric acid use on root surfaces previously affected by periodontal disease may favor clot stabilization and may have a beneficial effect on surgical outcomes. Also, EDTA can be used to neutralize citric acid effects on periodontal cells.
Keywords: Blood; Smear layer; Edetic acid; Citric acid